In silico epitope prediction, expression and functional analysis of Per a 10 allergen from the American cockroach - Tong, Xunliang (Int J Mol Med, 2016)
Cockroach (CR) allergies caused by the American cockroach hyave been recognized to be repsonsible for IgE-mediated type I hypersensitivity worldwide. Per a 10 is one of the recognized main allergens of the American CR. In a previous study, we examined another American CR allergen, Per a 9 in patients with CR allergies and examined epitope sequences in this allergen. In the present study, we aimed to examine epitope sequences in the Per a 10 allergen. for this purpose, the Per a 10 gene was cloned and expressed in Escherichia coli (E. coli) systems. Our results revealed that 9 out of 16 (56.3%) sera from patients with American CR allergies reacted to Per a10, as assessed by ELISA, confirming that Per a 10 is a major allergen of the American CR. Our results also revealed that the expression of CD63 and CCR3 on passively sensitized basophils (obtained sera of patients with American CR allergies) was increased by approximately 2.3-fold, indicating that recombinant Per a 10 is functionally active. In addition, 3 immunoinformatics tools, namely the DNAStar Protean system, the Bioinformatics Predicted Antigenic Peptides (BPAP) system and the BepiPred 1.0 server were used to predict the peptides and the results revealed 8 peptides (2–12, 55–67, 98–120, 125–133, 149–160, 170–182, 201–208 and 223–227) as potential B cell epitopes of the Per a 10 allergen. Moreover, Per a 10 was predicted to have 3 T cell epitope sequences, namely 83–92, 139–147 and 162–170. The findings of our study on the CR allergen may prove to be useful in the development of peptide-based vaccine for the prevention and/or treatment of CR allergies.